Muscle activity does not change in response to different loads during bench press - Kin Isler, A.; Asci, A.; Aritan, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Among the exercises used in heavy-resistance training programs, bench press is one of the most popular upper body lifts. Myoelectrical activity of upper-body muscles during bench press exercise has attracted a great deal of interest (Clemons & Aaron, 1997; Welsch et al. 2005) however limited research have been found related with the effects of different loads on electromyographical activity of upper body muscles during the bench press. Therefore the aim of this study was to determine if muscle activation changes in response to different loads during non-bar release concentric bench press motion.